Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper examines Iceland's expenditure policy, especially five expenditure pressure points, as well as capital flows and monetary policy effectiveness in small open economies. The postcrisis fiscal adjustment demanded painful choices, with spending on healthcare, education, and investment suffering cuts in real terms. While expenditures in these areas have rebounded more recently, there is a room for further decompression. Using quarterly panel data for 18 advanced and emerging small open economies during 2002-15, it finds that monetary policy is focused on inflation developments, but also that domestic interest rates affect capital flows, raising concerns about a reinforcing loop between monetary policy and capital flows.